In season power development of an English Premier League soccer player - Milligan, J. (Journal of Australian Strength and Conditioning, 2020)
The English Premier League is considered the most physically demanding professional soccer league in the world, and players must be able to press aggressively and repeatedly, win aerial duals, and frequently perform high intensity purposeful movements at significant moments in the game, demands that are underpinned by specific biomotor qualities and the physical capacity of players. This case study discussed the strength and conditioning program of an English Premier League central midfielder, whose aim was to improve their power production capabilities. A variety of methods were used to achieve this adaptation, including heavily loaded strength exercises, Olympic lifting derivatives, loaded and unloaded jump variations, other ballistic exercises, and the combination of these methods in contrast sets. The player was tested weekly using a simple countermovement jump protocol, performed on a dual force platform, and three diagnostic markers were tracked; jump height, using the flight time method, relative peak power, and flight time : contraction time, representing how explosive the strategy employed during the jumps was. The training program elicited positive gains across all three variables, represented by large percentage improvements and effect sizes, despite being performed towards the end of a long and demanding season, and alongside extremely high concurrent endurance demands from training and competition. Exposing professional soccer players to a training programme that demands a range of loads to be moved at varying velocities throughout every training week can develop explosive neuromuscular qualities which underpin successful performance on the pitch, whilst maximising player robustness and ensuring the player is available for training sessions and most importantly, matches.